KUALITAS LAYANAN SISTEM INFORMASI AKADEMIK MENGGUNAKAN METODE KANO - Sahfitri, Vivi; Yulianingsih, Evi (JURNAL ILMIAH MATRIK, 2015)
Implementation of information systems is one of the supporting facilities for the performance in an agency . Utilization of information system aims to facilitate the task of the user (user) in order to achieve savings in time, cost, and resources in decision-making. User Satisfaction is one factor or measure the success of the process of development and implementation of information system on an institution . This study analyzes the service quality information system using the method of Kano. Kano method used to identify the level of satisfaction and dissatisfaction through 25 services attributes to be used as an attribute in the study.